Rock Physics Model and Seismic Dispersion and Attenuation in Gas Hydrate-Bearing Sediments - Guo, Zhiqi; Wang, Xueying; Jiao, Jian; Chen, Haifeng (Frontiers in Earth Science, 2021)
A rock physics model was established to calculate the P-wave velocity dispersion and attenuation caused by the squirt flow of fluids in gas hydrate-bearing sediments. The critical hydrate saturation parameter was introduced to describe different ways of hydrate concentration, including the mode of pore filling and the co-existence mode of pore filling and particle cementation. Rock physical modeling results indicate that the P-wave velocity is insensitive to the increase in gas hydrate saturation for the mode of pore filling, while increases rapidly with increasing gas hydrate saturation for the co-existence mode of pore filling and particle cementation. Meanwhile, seismic modeling results show that both the PP and mode-converted PS reflections are insensitive to the gas hydrate saturation that is lower than the critical value, while tend to change obviously for the hydrate saturation that is higher than the critical value. These can be interpreted that only when gas hydrate begins to be part of solid matrix at high gas hydrate saturation, it represents observable impact on elastic properties of the gas hydrate-bearing sediments. Synthetic seismograms are calculated for a 2D heterogeneous model where the gas hydrate saturation varies vertically and layer thickness of the gas hydrate-bearing sediment varies laterally. Modeling results shows that larger thickness of the gas hydrate-bearing layer generally corresponds to stronger reflection amplitudes from the BSR.